Association between gout and erectile dysfunction: a systematic review and meta-analysis - Du, Xing-li; Liu, Lei; Song, Wen; Zhou, Xiang; Lv, Zheng-tao (PLOS ONE, 2016)
Background The aim of this systematic review and meta-analysis was to assess the possible association between gout and erectile dysfunction (ED). Methods Studies were identified by extensively searching EMBASE, Pubmed, CENTRAL and ISI Web of Science. Four electronic databases were searched from their inception date to the latest issue (March 2016), without language restriction. Each reviewer screened articles independently and was blinded to the findings of the other reviewer. Data was extracted in adherence to the predetermined data collection form and meta-analysis was conducted via RevMan 5.3. Results Five studies involving 56465 patients (mean age: 49.11 years) with gout and 155636 non-gout subjects (mean age: 48.76 years) were selected. The combination of unadjusted odds ratio (OR) showed that patients with gout were 1.44 times more likely to be diagnosed with ED when compared with control (95% confidence interval (95%CI) 1.20, 1.72). After adjustment for age and comorbidities, the heightened risk to develop ED was still present (1.18, 95%CI 1.02, 1.38). Subgroup-analysis by age showed statistically significant association of gout and ED in all age groups. However, evidence supporting a causal effect of gout on ED was insufficient. Conclusion The findings of this review indicated a positive association of gout and ED, but this work is hampered by the heterogeneity among included studies, to some extent. Future studies with larger community-based homogeneous population and randomized controlled trials aimed to evaluate the effect of gout treatment on ED associated outcomes are needed at this point.